Investigating two Possibilities in the Family Situation in Iran A Critique on the book The Decline of Patriarchy The Collapse of the Family or the Emergence of the Civil Family - Maryam Esakafi Noghani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book The Decline of Patriarchy, The Collapse of the Family, or the Advent of the Civil Family explores two possibilities in the family situation in Iran, which, according to the author, can exist simultaneously. With a critical approach, he has tried to evaluate policies and plans in the family and to find alternatives to the pathology of diagnosis and strategies. This article reviews the critical review of this book. The study of the structure, form, content, and method of research in this book showed that although the subject of the book is a very interesting, new topic and very attractive, there is a lot of research that could be the subject of future research and research dissertations. But this book has fundamental defects in the structure so it seems that while the book's contents are not well-integrated, the main contents are in the first part of the book, and the following sections repeat the first chapter. The content also has conceptual and theoretical contradictions, and the author's allegations do not have reason to believe persuasive arguments and evidence. The methodology also has ambiguities which, despite the title and good subject of the book, are not proposed to the students in the present form.